Study of the Effect of Cultural Integration, Marketing Innovation, and Brand Positioning on Brand Awareness in Indonesia - Sudirjo, Frans; Palembang, Septianti Permatasari; Desembrianita , Eva; Ode, Haruni; Radnan, Yokie (West Science Journal Economic and Entrepreneurship, 2024)
This research investigates the influence of cultural integration, marketing innovation, and brand positioning on brand awareness in the Indonesian market through quantitative analysis. Drawing on data from 200 participants, the study examines the relationships between these variables using correlation and regression analyses. The findings reveal significant positive correlations between cultural integration, marketing innovation, brand positioning, and brand awareness, indicating that brands that effectively integrate cultural elements, employ innovative marketing strategies, and establish strong brand positioning are more likely to enhance brand awareness among Indonesian consumers. Regression analysis further confirms the direct effects of cultural integration, marketing innovation, and brand positioning on brand awareness, while controlling for demographic variables. The study underscores the importance of cultural sensitivity, creativity, and strategic positioning in building strong brands in culturally diverse markets like Indonesia, offering valuable insights for marketers and brand managers seeking to navigate the complexities of the Indonesian market.